СУЧАСНИЙ СТАН ПРОБЛЕМИ ФОРМУВАННЯ КУЛЬТУРИ СПІЛКУВАННЯ МАЙБУТНІХ ПЕДАГОГІВ ЗАСОБАМИ ДІАЛОГІЧНИХ НАВЧАЛЬНИХ СИТУАЦІЙ (Педагогіка вищої та середньої школи, 2004)
The article deals with the various problems and aspects of communicational culture formation in dialogue training studying situation of professional orientation.